Supramaximal Horizontal Rectus Recession–Resection Surgery for Complete Unilateral Abducens Nerve Palsy - Wang, Zhonghao; Fu, Licheng; Shen, Tao; Qiu, Xuan; Yu, Xinping; Shen, Huangxuan; Yan, Jianhua (Frontiers in Medicine, 2022)
Abstract Purpose: Review the surgical procedures and outcomes of supramaximal horizontal rectus recession-resection surgery for abduction deficiency and esotropia resulting from complete unilateral abducens nerve palsy. Methods: A total of 36 consecutive cases diagnosed as complete abducens nerve palsy receiving supramaximal medial rectus recession (8.5±1.4 mm, range: 6~10) combined with a supramaximal lateral rectus resection (11.1±1.7 mm, range: 8~14) as performed over the period from 2017 to 2020 were reviewed retrospectively. All surgeries were performed by a single surgeon. Pre- and post-operative ocular motility, ocular alignment, forced duction test, binocular vision, abnormal head posture and surgical complications were assessed. Results: Of these 36 cases, 23 (63.8%) were followed up for greater than 2 months (Mean+SD = 8.4±6.0, range: 2-24) after surgery and data presented are from these 23 patients. Mean+SD age of these patients was 41.7±14.4 (range: 12-67) years with 73.9% being female. Trauma (52.2%, 12/23) and cerebral lesions (21.7%, 5/23) were the primary etiologies for this condition. Esodeviation in primary position improved from 55.5±27.2 PD (range: 25-123) to 0.04±7.3 PD (range: -18-12) as assessed on their last visit. Pre-operative abduction deficits of -5.6±1.0 (range: -8--4) were reduced to -2.4±1.4 (range: -4-0) post-operatively. The mean dose-effect coefficient of 2.80±1.20 PD/mm (range:1.07-6.05) was positively correlated with pre-operative esodeviation. Rates of overcorrection and ortho were 69.6% and 26.1%, respectively on the 1st day after surgery and achieved respective levels of 4.3% and 82.6% on their last visit. Conclusion: Supramaximal horizontal rectus recession-resection surgery is an effective treatment method for a complete abduction deficiency. The dose-effect was positively correlated with pre-operative esodeviation. Overcorrection on the first day post-operatively is required for a long-term satisfactory surgical outcome.